Environmentally friendly and degradable composite dust suppressant and preparation method thereof

By combining the modified silane coupling agent, film forming agent, thickener and antifreeze, a composite dust inhibitor with water absorption and flame retardant is formed, which solves the problem of the reduction in efficiency of existing dust inhibitors in harsh environments. , achieving efficient and multi-functional dust suppression effect.

CN118956348BActive Publication Date: 2025-01-03SOUTH CHINA INST OF ENVIRONMENTAL SCI MEP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411420909.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing environmentally friendly and degradable dust inhibitors have reduced dust suppression efficiency in harsh environments such as low or high temperatures, and their functional range is limited, making it difficult to adapt to complex and changeable environmental conditions.

Method used

Modified silane coupling agent is used to open the ring reaction and phosphorylation of acrylic acid and silane coupling agent KH-560 to form a compound containing acrylate groups, silicon elements and phosphorus elements, combining film forming agents, thickening agents and antifreeze The agent forms a composite dust inhibitor with water absorption, film formation and flame retardant properties.

Benefits of technology

It improves the dust suppression efficiency, moisturizing properties and flame retardant properties of dust inhibitors, can effectively control dust in a variety of complex environments, and broadens the application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention discloses an environmentally friendly and degradable composite dust suppressant, comprising the following raw materials in parts by weight: 10-50 parts of a film former, 10-50 parts of a thickener, 1-3 parts of a surfactant, 0.1-2 parts of a modified silane coupling agent, and 0.1-1.5 parts of an antifreeze agent, wherein the modified silane coupling agent not only introduces two flame retardant elements, silicon and phosphorus, but also introduces an acrylate group with excellent film-forming and moisture-retaining properties, thereby giving the dust suppressant a variety of properties; the invention also discloses a preparation method of the environmentally friendly and degradable composite dust suppressant. The environmentally friendly and degradable composite dust suppressant provided by the invention has high dust suppression efficiency, good moisture retention and film-forming properties, high viscosity, and excellent flame retardant properties, and can significantly and effectively reduce the potential harm caused by dust to passing pedestrians and vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dust suppressants, and in particular to an environmentally friendly and degradable composite dust suppressant and a preparation method thereof. Background Art

[0002] In addressing the challenge of dust pollution, dust suppressants play a vital role. They are a class of chemicals specially designed to control and reduce suspended particulate matter in the air. By forming a protective film on the surface of dust, dust suppressants can lock in fine dust particles and prevent them from being blown away by the wind, thereby effectively reducing the dust concentration in the air. The application of this technology not only helps to improve air quality and protect people's respiratory health, but also reduces the adverse impact on the environment. It is one of the important means to achieve environmental protection and sustainable development goals. With the increasing demand for environmentally friendly products, the research and development of efficient and environmentally friendly dust suppressants has become an important research direction in the field of environmental science.

[0003] The patent with application number CN202111621344.0 discloses an environmentally friendly and degradable dust suppressant and its preparation method. The environmentally friendly and degradable dust suppressant includes the following raw materials: hydrolyzed extract of Spartina alterniflora, starch, sodium alginate, sodium sulfate, polyethylene glycol, polyvinyl alcohol, dispersant and cross-linking agent. The environmentally friendly and degradable dust suppressant provided by this invention uses the coastal invasive plant Spartina alterniflora as the main raw material, and uses substances such as soluble total sugar and soluble fiber of Spartina alterniflora to undergo cross-linking and graft copolymerization with the functional groups of other components of the dust suppressant to form a network structure, so that the dust suppressant has strong dust suppression performance. In addition, the dust suppressant dispersion system is stable and has strong permeability. It can significantly reduce interfacial tension, make the formed micelle structure denser, quickly and efficiently capture and condense dust particles in the air, form a solidified film, and improve the dust suppression efficiency; the patent with application number CN202211439381.4 discloses an environmentally friendly and degradable dust suppressant. A shape-retaining high-wettability dust suppressant and a preparation method thereof, comprising the following raw materials: sodium fatty acid methyl ester sulfonate, a penetrant, sodium alginate, sodium chloride, and water, wherein the dust suppressant is a network chain structure; the dust suppressant of the invention significantly improves the ability of coal powder particles to quickly condense and settle in the air, thereby achieving a higher dust reduction efficiency and reducing costs, is non-toxic and harmless to the human body and the environment, has strong wettability, good water retention, and significant dust suppression effects; however, the functional range of these two dust suppressants is relatively limited, and the dust suppression efficiency will be reduced in harsh environments such as low or high temperatures, which to a certain extent restricts their application effects in a wider range of scenarios.

[0004] Therefore, there is an urgent need to develop a biodegradable composite dust suppressant that is environmentally friendly and healthy, has high dust suppression efficiency, and has antifreeze and flame retardant properties, so that it can better adapt to various complex and changeable environmental conditions to effectively control dust and protect the atmospheric environment. Summary of the invention

[0005] The purpose of the present invention is to provide an environmentally friendly and degradable composite dust suppressant and a preparation method thereof in view of the deficiencies of the prior art. The environmentally friendly and degradable composite dust suppressant prepared by the present invention has a highly efficient dust suppression effect and has moisture retention, flame retardancy and antifreeze properties.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] An environmentally friendly and degradable composite dust suppressant comprises the following raw materials in parts by weight: 10-50 parts of a film former, 10-50 parts of a thickener, 1-3 parts of a surfactant, 0.1-2 parts of a modified silane coupling agent, and 0.1-1.5 parts of an antifreeze agent; the preparation method of the modified silane coupling agent is as follows:

[0008] Step S1, adding silane coupling agent KH-560, acrylic acid, and chromium isooctanoate to toluene at 70-80° C. with stirring, reacting for 3-5 hours, cooling to room temperature, and removing the solvent to obtain an intermediate;

[0009] Step S2, adding the intermediate obtained in step S1, aluminum chloride and dimethyl phosphoric acid to N,N-dimethylformamide at 100-110° C. with stirring, reacting for 6-8 hours, cooling to room temperature, and obtaining a modified silane coupling agent after purification;

[0010] The synthetic route of modified silane coupling agent is as follows:

[0011] ;

[0012] .

[0013] Furthermore, the film-forming agent is one or more of polyethylene glycol, polyvinyl alcohol, and water-soluble polyvinyl alcohol fiber.

[0014] Furthermore, the thickener is one or more of carboxymethyl cellulose, hydroxyethyl cellulose, pectin and gelatin.

[0015] Furthermore, the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, nonylphenol polyoxyethylene ether, polyacrylamide, and fatty alcohol polyoxyethylene ether.

[0016] Furthermore, the antifreeze agent is one or more of calcium chloride, sodium chloride and sodium silicate.

[0017] Furthermore, in step S1, the mass ratio of acrylic acid, silane coupling agent KH-560, and chromium isooctanoate is 10:12-17:0.5-0.8, and the amount of acrylic acid added to toluene is 5-6 g / 100 mL.

[0018] Furthermore, in step S2, the mass ratio of the intermediate, aluminum chloride and dimethyl phosphoric acid is 10:2.5-4:2-3, and the amount of dimethyl phosphoric acid added to N,N-dimethylformamide is 10-15 g / 100 mL.

[0019] The present invention also provides a method for preparing an environmentally friendly and degradable composite dust suppressant, comprising the following steps:

[0020] (1) Prepare the following components according to the proportions: film former, thickener, surfactant, modified silane coupling agent, and antifreeze agent;

[0021] (2) Add the film-forming agent and thickener to deionized water at 80-100°C, stir until completely dissolved, and cool to room temperature to obtain a mixed solution;

[0022] (3) The mixed solution obtained in step (2), the surfactant, the modified silane coupling agent and the antifreeze agent are mixed evenly, and then the mixture is heated to 50-70° C. and stirred for reaction for 0.5-1 h, and then cooled to room temperature to obtain the product.

[0023] Furthermore, in step (2), the mass ratio of the film-forming agent to deionized water is 1:10-12.

[0024] The present invention has the following beneficial effects:

[0025] The present invention prepares the modified silane coupling agent by chemical modification. First, the carboxyl group of acrylic acid and the epoxy group of the silane coupling agent KH-560 undergo a ring-opening reaction to obtain an intermediate containing a hydroxyl group. Then, phosphoric acid and the intermediate undergo an esterification reaction to obtain the modified silane coupling agent. The modified silane coupling agent contains an acrylate group, a silicon element, and a phosphorus element in its structure. The acrylate group has significant water absorption and film-forming properties. These properties enable the material to absorb and lock in moisture, prevent excessive loss of moisture, and thus achieve a moisturizing effect. The compound containing the phosphorus element can be decomposed to obtain a strong dehydrating agent, polymetaphosphoric acid, which can promote rapid surface dehydration of oxygen-containing materials. Dehydration and carbonization form a non-combustible carbon layer, which can isolate air and heat to prevent the further spread of fire. At the same time, it can release PO· free radicals to capture and neutralize H· free radicals and HO· free radicals produced during combustion, thereby interrupting the chain reaction of combustion and reducing combustion intensity. Silicon element can form an enrichment layer on the surface of the material through the migration mechanism during the combustion process, effectively reducing the contact between oxygen and combustible gas, thereby achieving the purpose of flame retardancy. Phosphorus-containing compounds can promote the formation of carbon layers at high temperatures, while silicon-containing compounds can increase the thermal stability of these carbon layers. The two work together to make the material have a more stable and effective flame retardant effect.

[0026] The present invention compounds a film former, a thickener, a surfactant, a modified silane coupling agent, and an antifreeze agent, and adopts environmentally friendly and degradable materials. After the raw materials react, an environmentally friendly and degradable composite dust suppressant is obtained, wherein the modified silane coupling agent can establish an effective chemical bond between the interfaces of organic materials such as film formers and thickeners and inorganic materials of antifreeze agents, significantly improving the bonding strength between materials and the compatibility of each component of the dust suppressant system, improving the viscosity of the dust suppressant, and thus improving the dust suppression efficiency. The environmentally friendly and degradable composite dust suppressant of the present invention has the characteristics of high dust suppression efficiency, good moisture retention and film forming properties, high viscosity, and excellent flame retardant properties. The multifunctional dust suppressant can be widely used in a variety of complex environments, thereby greatly broadening the application field and meeting the dust suppression needs in different scenarios. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] The raw materials used in the following examples are all common commercial products. Polyethylene glycol has a molecular weight of 4000 and is purchased from Yunsheng Chemical (Shandong) Co., Ltd.; polyvinyl alcohol is polyvinyl alcohol 2488, purchased from Jinan Guangxun Trading Co., Ltd.; water-soluble polyvinyl alcohol fiber, length 12 mm, brand Futai, purchased from Shandong Futai Fiber Co., Ltd.; carboxymethyl cellulose, viscosity 50-100mpa·s, molecular weight 90000, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; hydroxyethyl cellulose, viscosity 30000-100000 (mpa.s 2% 20℃ aqueous solution), brand Leweisi, purchased from Jinan Kaichuang Chemical Co., Ltd.; pectin EINECS No. 232-553-0, gelatin EINECS No. 203-740-4, both purchased from Jiangxi Huayuyuan Biotechnology Co., Ltd.; sodium silicate is sodium metasilicate pentahydrate, purchased from Jinan Junteng Chemical Co., Ltd.

[0029] Example 1: An environmentally friendly and degradable composite dust suppressant, comprising the following raw materials in parts by weight: 10 parts of a film former, 50 parts of a thickener, 1 part of a surfactant, 0.1 parts of a modified silane coupling agent, and 0.1 parts of an antifreeze agent;

[0030] The film former is polyvinyl alcohol 2488, the thickener is carboxymethyl cellulose, the surfactant is sodium dodecylbenzene sulfonate, and the antifreeze is calcium chloride;

[0031] The preparation method of the modified silane coupling agent is as follows:

[0032] Step S1, adding 12 g of silane coupling agent KH-560, 10 g of acrylic acid, and 0.5 g of chromium isooctanoate to 200 mL of toluene at 70° C. with stirring, reacting for 5 h, cooling to room temperature, and filtering to obtain a filtrate, then rotary evaporating the filtrate to remove toluene at a temperature of 60° C., a rotation rate of 120 rpm, and a vacuum degree of -0.08-0.1 MPa to obtain an intermediate;

[0033] Step S2, adding 10 g of the intermediate obtained in step S1, 2.5 g of aluminum chloride and 2 g of dimethyl phosphoric acid to 20 mL of N,N-dimethylformamide at 100° C. with stirring, reacting for 8 h, cooling to room temperature and filtering to obtain a filtrate, then rotary evaporating the filtrate at a temperature of 80° C., a rotation rate of 120 rpm and a vacuum degree of 25-50 mbar to remove N,N-dimethylformamide to obtain a modified silane coupling agent;

[0034] The synthetic route of modified silane coupling agent is as follows:

[0035] ;

[0036] ;

[0037] The NMR results of the modified silane coupling agent are: 1 H NMR (300 MHz, acetone-d6) δ 6.41 (d, 1H), 6.10-6.22 (m, 1H), 5.83 (d, 1H), 4.86-4.99 (m, 1H), 4.34-4.59 (m, 2H), 3.56-3.81 (m, 2H), 3.48-3.61 (m, 9H), 3.35 (t, 2H), 1.36-1.54 (m, 2H), 1.26 (d, 6H), 0.56 (t, 2H).

[0038] A method for preparing an environmentally friendly and degradable composite dust suppressant comprises the following steps:

[0039] (1) Prepare the following components according to the proportions: film former, thickener, surfactant, modified silane coupling agent, and antifreeze agent;

[0040] (2) adding the film-forming agent and the thickener into deionized water at 80°C, stirring until completely dissolved, and cooling to room temperature to obtain a mixed solution, wherein the mass ratio of the film-forming agent to deionized water is 1:10;

[0041] (3) The mixed solution obtained in step (2), the surfactant, the modified silane coupling agent and the antifreeze agent are mixed evenly, then heated to 50° C. and stirred for reaction for 1 hour, and then cooled to room temperature to obtain the product.

[0042] Example 2: An environmentally friendly and degradable composite dust suppressant, comprising the following raw materials in parts by weight: 50 parts of a film former, 10 parts of a thickener, 3 parts of a surfactant, 2 parts of a modified silane coupling agent, and 1.5 parts of an antifreeze agent;

[0043] The film-forming agent is water-soluble polyvinyl alcohol fiber, the thickener is pectin, the surfactant is nonylphenol polyoxyethylene ether, and the antifreeze agent is calcium chloride;

[0044] The preparation method of the modified silane coupling agent is as follows:

[0045] Step S1, adding 17 g of silane coupling agent KH-560, 10 g of acrylic acid, and 0.8 g of chromium isooctanoate to 166.67 mL of toluene at 80° C. with stirring, reacting for 3 h, cooling to room temperature, and filtering to obtain a filtrate, then rotary evaporating the filtrate to remove toluene at a temperature of 60° C., a rotation rate of 120 rpm, and a vacuum degree of -0.08-0.1 MPa to obtain an intermediate;

[0046] Step S2, adding 10 g of the intermediate obtained in step S1, 4 g of aluminum chloride and 3 g of dimethyl phosphoric acid to 20 mL of N,N-dimethylformamide at 110° C. with stirring, reacting for 6 h, cooling to room temperature and filtering to obtain a filtrate, then rotary evaporating the filtrate at a temperature of 80° C., a rotation rate of 120 rpm and a vacuum degree of 25-50 mbar to remove N,N-dimethylformamide to obtain a modified silane coupling agent;

[0047] A method for preparing an environmentally friendly and degradable composite dust suppressant comprises the following steps:

[0048] (1) Prepare the following components according to the proportions: film former, thickener, surfactant, modified silane coupling agent, and antifreeze agent;

[0049] (2) adding a film-forming agent and a thickener into deionized water at 80°C, stirring until completely dissolved, and cooling to room temperature to obtain a mixed solution, wherein the mass ratio of the film-forming agent to deionized water is 1:12;

[0050] (3) The mixed solution obtained in step (2), the surfactant, the modified silane coupling agent and the antifreeze agent are mixed evenly, and then the mixture is heated to 70° C. and stirred for reaction for 0.5 h, and then cooled to room temperature to obtain the product.

[0051] Example 3: An environmentally friendly and degradable composite dust suppressant, comprising the following raw materials in parts by weight: 30 parts of a film former, 20 parts of a thickener, 2 parts of a surfactant, 1 part of a modified silane coupling agent, and 1 part of an antifreeze agent;

[0052] The film former is polyethylene glycol, the thickener is hydroxyethyl cellulose, the surfactant is fatty alcohol polyoxyethylene ether, and the antifreeze is sodium chloride;

[0053] The preparation method of the modified silane coupling agent is as follows:

[0054] Step S1, adding 15g of silane coupling agent KH-560, 10g of acrylic acid, and 0.6g of chromium isooctanoate to 181.82mL of toluene at 75°C with stirring, reacting for 4h, cooling to room temperature, and filtering to obtain a filtrate, then rotary evaporating the filtrate to remove toluene at a temperature of 60°C, a rotation rate of 120 rpm, and a vacuum degree of -0.08-0.1 MPa to obtain an intermediate;

[0055] Step S2, adding 10 g of the intermediate obtained in step S1, 3 g of aluminum chloride and 2.5 g of dimethyl phosphoric acid to 20 mL of N,N-dimethylformamide at 105° C. with stirring, reacting for 7 h, cooling to room temperature and filtering to obtain a filtrate, then rotary evaporating the filtrate at a temperature of 80° C., a rotation rate of 120 rpm and a vacuum degree of 25-50 mbar to remove N,N-dimethylformamide to obtain a modified silane coupling agent;

[0056] A method for preparing an environmentally friendly and degradable composite dust suppressant comprises the following steps:

[0057] (1) Prepare the following components according to the proportions: film former, thickener, surfactant, modified silane coupling agent, and antifreeze agent;

[0058] (2) adding a film-forming agent and a thickener into deionized water at 90°C, stirring until completely dissolved, and cooling to room temperature to obtain a mixed solution, wherein the mass ratio of the film-forming agent to deionized water is 1:11;

[0059] (3) The mixed solution obtained in step (2), the surfactant, the modified silane coupling agent and the antifreeze agent are mixed evenly, then heated to 60° C. and stirred for reaction for 40 minutes, and then cooled to room temperature to obtain the product.

[0060] Comparative Example 1: An environmentally friendly and degradable composite dust suppressant, comprising the following raw materials in parts by weight: 30 parts of a film former, 5 parts of a thickener, 0.5 parts of a surfactant, 1 part of a modified silane coupling agent, and 0.1 parts of an antifreeze agent;

[0061] The film former is polyethylene glycol, the thickener is hydroxyethyl cellulose, the surfactant is fatty alcohol polyoxyethylene ether, and the antifreeze is sodium chloride;

[0062] The preparation method of the modified silane coupling agent is as follows:

[0063] 15 g of silane coupling agent KH-560, 10 g of acrylic acid, and 0.6 g of chromium isooctanoate were added to 181.82 mL of toluene at 60° C. with stirring, and reacted for 3 h. After cooling to room temperature, the mixture was filtered to obtain a filtrate, and then the filtrate was evaporated to remove toluene at a temperature of 60° C., a rotation rate of 120 rpm, and a vacuum degree of -0.08-0.1 MPa to obtain a modified silane coupling agent;

[0064] A method for preparing an environmentally friendly and degradable composite dust suppressant comprises the following steps:

[0065] (1) Prepare the following components according to the proportions: film former, thickener, surfactant, modified silane coupling agent, and antifreeze agent;

[0066] (2) adding a film-forming agent and a thickener into deionized water at 90°C, stirring until completely dissolved, and cooling to room temperature to obtain a mixed solution, wherein the mass ratio of the film-forming agent to deionized water is 1:11;

[0067] (3) The mixed solution obtained in step (2), the surfactant, the modified silane coupling agent and the antifreeze agent are mixed evenly, then heated to 50° C. and stirred for reaction for 20 min, and then cooled to room temperature to obtain the product.

[0068] Comparative Example 2: An environmentally friendly and degradable composite dust suppressant, comprising the following raw materials in parts by weight: 30 parts of a film former, 5 parts of a thickener, 0.5 parts of a surfactant, 1 part of a silane coupling agent, and 0.1 parts of an antifreeze agent;

[0069] The film former is polyethylene glycol, the thickener is hydroxyethyl cellulose, the surfactant is fatty alcohol polyoxyethylene ether, the antifreeze agent is sodium chloride, and the silane coupling agent is KH-560;

[0070] A method for preparing an environmentally friendly and degradable composite dust suppressant comprises the following steps:

[0071] (1) Prepare the following components according to the proportions: film former, thickener, surfactant, modified silane coupling agent, and antifreeze agent;

[0072] (2) adding a film-forming agent and a thickener into deionized water at 90°C, stirring until completely dissolved, and cooling to room temperature to obtain a mixed solution, wherein the mass ratio of the film-forming agent to deionized water is 1:11;

[0073] (3) The mixed solution obtained in step (2), the surfactant, the silane coupling agent and the antifreeze agent are mixed evenly, then heated to 50° C. and stirred for reaction for 20 min, and then cooled to room temperature to obtain the product.

[0074] The performance of the environmentally friendly and degradable composite dust suppressants prepared in Examples 1-3 and Comparative Examples 1-2 was tested. The test method is as follows. The test results are shown in Table 1 below.

[0075] (1) Dust suppression efficiency

[0076] The dust suppressants prepared in Examples 1-3 and Comparative Examples 1-2 were diluted with 5 times the mass of clean water to obtain dust suppressant emulsions. The mass of the glass plate was weighed and recorded as m 1 (g); Take 3 mL of the prepared dust suppressant emulsion and evenly apply it on the glass plate. Measure the mass of the glass plate and the dust suppressant emulsion, recorded as m 2 (g); After the dust suppressant emulsion on the glass plate is completely dried to form a film, the mass of the glass plate and the dust suppressant film is measured and recorded as m 3 (g), then moisture content (%) = (m 2 -m 3 ) / (m 2 -m 1 )×100%, the moisture content is recorded as M.

[0077] Place a dust sample of 10 mesh or less and dried at 50°C for 300 minutes in a petri dish, weigh the mass of the dust sample, and record it as N (g). Place the prepared dust suppressant emulsion (the dust suppressant is diluted with 5 times the mass of clean water) in a sprayer and spray it evenly on the surface of the dust sample. Measure the total mass of the petri dish, dust sample and dust suppressant emulsion, and record it as n. 1 (g). After a solidified layer is formed on the surface of the dust sample, the dust covered with dust suppressant is subjected to a wind resistance test, that is, a blower is used to simulate natural wind, and the dust covered with dust suppressant is blown continuously for 30 minutes, and then the total mass of the dust pile and the culture dish blown by the wind is weighed, recorded as n 2 (g), then dust suppression efficiency (%) = [n 2 - (n 1 -N) (1-M)] / N×100%.

[0078] (2) Surface tension and viscosity

[0079] The surface tension is tested according to the plate method in GB / T22237-2008 "Determination of surface tension of surfactants". The viscosity is measured according to the method specified in GB / T10247-2008 "Viscosity measurement method".

[0080] Moisturizing rate and film-forming property

[0081] Weigh a certain mass of dust sample of 10 mesh or less and dried at 50°C for 300 min and spread it flat in a petri dish. The mass of the petri dish is recorded as m (g). Then spray a certain amount of dust suppressant solution evenly on the surface of the dust sample. The mass of the petri dish after adding the dust suppressant solution is recorded as m. 0(g), after the dust suppressant penetrates into the dust sample, the culture dish is placed in a constant temperature drying oven at 40°C and dried for 6 hours. At this time, the weight of the culture dish is m 6 (g), then the moisture retention rate (%) = (m 6 -m) / (m 0 -m)×100%; the film-forming property of the dust suppressant is judged based on the quality and integrity of the film formed after the dust suppressant is sprayed onto the surface of the dust sample.

[0082] Flame retardant properties

[0083] Take 2 30g dust samples of 10 mesh and below and dried at 50°C for 300min, respectively, and treat them with 2% dust suppressant solution and water (both 30g), and put them into 2 three-necked flasks after drying. Connect the flasks to an air pump and put in a thermometer. Set the gas flow rate at 250mL / min, then place the flasks in an 80°C oil bath and heat to 150°C. Use a CO gas detector to detect the CO concentration and record the CO concentration at this time. The inhibition rate (%) = (S 1 -S 2 ) / S 1 ×100%,S 1 (g / L) is the CO concentration emitted by the dust sample after water treatment; S 2 (g / L) is the CO concentration emitted from the dust sample treated with dust suppressant.

[0084] Table 1 Tests on dust suppression efficiency, surface tension and viscosity, moisture retention and film-forming properties, and flame retardant properties of environmentally friendly and biodegradable composite dust suppressants

[0085] sample Moisture content (%) Dust suppression efficiency (%) Surface tension (mN / m) Viscosity (mPa.s) Moisture retention rate (%) Film forming properties Inhibition rate (%) Example 1 85.11 98.31 18.5 47 48.96 The surface is smooth and flat, without cracks 95.36 Example 2 86.25 98.18 19.1 46 48.37 The surface is smooth and flat, without cracks 95.28 Example 3 85.87 97.39 19.4 44 47.99 The surface is smooth and flat, without cracks 94.99 Comparative Example 1 89.66 86.26 28.7 32 41.51 The surface is intact overall, but there are small cracks 83.54 Comparative Example 2 90.43 81.65 29.2 30 26.89 The surface is intact overall, but there are small cracks 82.11

[0086] As can be seen from Table 1, the moisture content of the dust suppressants prepared in Examples 1-3 is relatively stable, so the performance of the dust suppressants is stable and the moisture retention rate is high. The higher moisture retention rate can keep the dust surface moist for a longer period of time, thereby effectively suppressing the flying of dust. It has excellent film-forming properties and can quickly solidify into a film on the dust surface to form a continuous film with certain strength and toughness. This film can effectively prevent the dust from being raised again due to wind, vibration and other reasons, thereby improving the dust suppression efficiency of the dust suppressant. The moisture content of the dust suppressants prepared in Comparative Examples 1-2 is relatively high, which may affect the moisture retention rate, film-forming properties and other properties of the dust suppressants, thereby reducing their dust suppression efficiency; the dust suppressants prepared in Examples 1-3 have lower surface tension and higher viscosity. This helps the dust suppressant to better wet the dust particles, promote the agglomeration and sedimentation of the dust, and ensure that the dust suppressant can evenly cover the dust surface to form a continuous and firm film. The dust suppressant prepared in Comparative Examples 1-2 has high surface tension and low viscosity, making it difficult to effectively wet the dust particles and may not be able to form a good film, thereby affecting its dust suppression effect. The dust suppressant prepared in Examples 1-3 has a high resistance rate. The dust suppressant with a high resistance rate forms an effective protective layer on the surface of the material, preventing the material from contacting with oxygen, thereby reducing the oxidation rate of the material and the generation of CO, indicating that the dust suppressant has good flame retardant properties. The dust suppressant prepared in Comparative Examples 1-2 only contains silicon and no phosphorus is introduced, so it has a low resistance rate and a poor flame retardant effect.

[0087] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0088] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. An environmentally friendly and degradable composite dust suppressant, characterized in that: The invention comprises the following raw materials in parts by weight: 10-50 parts of a film former, 10-50 parts of a thickener, 1-3 parts of a surfactant, 0.1-2 parts of a modified silane coupling agent, and 0.1-1.5 parts of an antifreeze agent; the preparation method of the modified silane coupling agent is as follows: Step S1, adding silane coupling agent KH-560, acrylic acid, and chromium isooctanoate to toluene at 70-80° C. with stirring, reacting for 3-5 hours, cooling to room temperature, and removing the solvent to obtain an intermediate, the structural formula of the intermediate is: ; Step S2, adding the intermediate obtained in step S1, aluminum chloride and dimethyl phosphoric acid to N,N-dimethylformamide at 100-110° C. with stirring, reacting for 6-8 hours, cooling to room temperature, and obtaining a modified silane coupling agent after purification. The structural formula of the modified silane coupling agent is: ; The film-forming agent is one or more of polyethylene glycol, polyvinyl alcohol, and water-soluble polyvinyl alcohol fiber; The thickener is one or more of carboxymethyl cellulose, hydroxyethyl cellulose, pectin and gelatin.

2. The environmentally friendly and degradable composite dust suppressant according to claim 1, characterized in that: The surfactant is one or more of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, nonylphenol polyoxyethylene ether, polyacrylamide, and fatty alcohol polyoxyethylene ether.

3. The environmentally friendly and degradable composite dust suppressant according to claim 1, characterized in that: The antifreeze agent is one or more of calcium chloride, sodium chloride and sodium silicate.

4. The environmentally friendly and degradable composite dust suppressant according to claim 1, characterized in that: The mass ratio of acrylic acid, silane coupling agent KH-560 and chromium isooctanoate in step S1 is 10:12-17:0.5-0.8, and the amount of acrylic acid added to toluene is 5-6 g / 100 mL.

5. The environmentally friendly and degradable composite dust suppressant according to claim 1, characterized in that: The mass ratio of the intermediate, aluminum chloride and dimethyl phosphoric acid in step S2 is 10:2.5-4:2-3, and the amount of dimethyl phosphoric acid added to N,N-dimethylformamide is 10-15 g / 100 mL.

6. The method for preparing the environmentally friendly and degradable composite dust suppressant according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Add the film-forming agent and thickener to deionized water at 80-100°C, stir until completely dissolved, and cool to room temperature to obtain a mixed solution; (2) The mixed solution obtained in step (1), the surfactant, the modified silane coupling agent and the antifreeze agent are mixed evenly, and then the mixture is heated to 50-70° C. and stirred for reaction for 0.5-1 h, and then cooled to room temperature to obtain the product.

7. The method for preparing the environmentally friendly and degradable composite dust suppressant according to claim 6, characterized in that: The mass ratio of the film-forming agent to deionized water in step (1) is 1:10-12.